Cycle of Fear in Learning: The Case for Three Language Skills - Rahmat, Noor Hanim (American Journal of Social Sciences and Humanities, 2019)
Fear or anxiety in learning is a vicious cycle. A reaction at one stage may lead to consequences at another stage. The fear of learning sometimes gives negative impact on a learner’s future learning encounters. The feeling of fear may hinder further learning experience possibilities. Studies on language learning have revealed that the fear of learning language skills influences learners’ perception of language skills. This paper presents the cycle of fear in language learning from the perspectives of speaking, reading and writing skills. Past studies in fear of readings reveal that learners’ choice of language strategies and their perception of reading difficulties influence their reading skill. Past research on writing found that fear of writing stems from the learners’ perception, the writing task and also the environment. Fear of oral presentation is caused by trait and state apprehension. The concept of fear of language learning can be summarized from common fears found in all the three past studies on language skills.